One-pot synthesis of MgFe2O4 nanospheres by solvothermal method - Shen, Y.; Wu, Y.; Li, Xin Yong; Zhao, Q.; Hou, Y. (2013)
Spinel MgFe2O4 nanospheres were successfully fabricated via an environmental friendly one-step solvothermal reduction method without employing any templates, complex apparatus or techniques. The structure, morphology and composition of the products were characterized by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and Fourier transform infrared spectrum, and their light-absorbing properties were obtained from UV-vis diffuse reflection spectrum. The results showed that the average diameter of the spheres was about 370 nm and the band-gap energy of the products was about 1.81 eV. They could be used as visible light responsive catalysts and also as templates to fabricate other inorganic or organic functional materials with well-defined nanostructures and improved performances. © 2013 Elsevier B.V.